Pendampingan Pembukuan Dan Pencatatan Keuangan Bagi Pelaku Usaha Mikro Kecil Di Desa Suliliran Baru - Mariyah, Mariyah; Rerung, Gusti Sampe (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Micro, Small, Medium Entreprises (MSMEs) have an important role to increase the economic growth, but MSMEs face problems in financial accounting amd records. Lack of understanding of financial accounting practices and not accurate in financial records is an obstacle for MSMEs to optimize their performance and business growth. The purpose of community services was to provide a simple financial accounting and recording assistance for MSMEs in Suliliran Baru village. Community services activities include: identifying problem in MMSEs, cash management, and preparing financial report. The method used consist ofdelivering material about financial accounting, training, and assistance for recording daily transactions. The results community service was to increase MSMEs owners in managing financial accounting and to be organize the financial records. The skills acquired can help MSMEs in making better business decisions and more effective financial management. Keywords: Business, Accounting, Financial Records, Transaction, MSMEs.